2015
DOI: 10.1002/hed.24059
|View full text |Cite
|
Sign up to set email alerts
|

Decision management in transoral robotic surgery: Indications, individual patient selection, and role in the multidisciplinary treatment for head and neck cancer from a European perspective

Abstract: A consensus regarding the indications of TORS and its role in the multidisciplinary management of HNSCC is to be established. © 2015 Wiley Periodicals, Inc. Head Neck 38: E2190-E2196, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 36 publications
1
39
0
4
Order By: Relevance
“…Only 1.0% of TORS patients compared to 5.1% of open surgery patients had fistula formation [3]. These are in line with other non-comparative studies which reported that TORS shortens the time to resumption of ambulation and speech functions and are related to lower rates of postoperative complications such as infections and fistula formation [6], [7], [8], [9]. Despite these known advantages, we report a case here to illustrate the possibility of invasive candidiasis in a patient who has undergone TORS.…”
Section: Introductionsupporting
confidence: 79%
“…Only 1.0% of TORS patients compared to 5.1% of open surgery patients had fistula formation [3]. These are in line with other non-comparative studies which reported that TORS shortens the time to resumption of ambulation and speech functions and are related to lower rates of postoperative complications such as infections and fistula formation [6], [7], [8], [9]. Despite these known advantages, we report a case here to illustrate the possibility of invasive candidiasis in a patient who has undergone TORS.…”
Section: Introductionsupporting
confidence: 79%
“…The use of less toxic treatment options is often recommended in the management of HPV p16-positive OPSCC because the patients are younger and display a better 5-year survival rate than patients with HPV-negative OPSCC 1314…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1990s, organ preservation trials demonstrated survival benefits of chemoradiotherapy (CRT) over radiotherapy (RT) alone, 9 leading to increased use of CRT in the early 2000s. 10, 11 However, there has recently been renewed enthusiasm for primary surgical approaches for the treatment of OPSCC 12–14 . This has been driven by technologic advances such as transoral robotic surgery (TORS) that enhance the feasibility of surgery for low T classification OPSCC and offer the potential of avoiding or de-escalating adjuvant treatments.…”
Section: Introductionmentioning
confidence: 99%